Pragmatic AI in education and its role in mathematics learning and teaching - Florence Gabriel; JohnPaul Kennedy; Rebecca Marrone; Simon Leonard (npj Science of Learning)
Pragmatic, scalable and sustainable responses to persistent socio-emotional issues such as mathematics anxiety remain elusive. Artificial intelligence (AI) offers a promising approach by enhancing students’ perceptions of competence, control, and value while transforming teacher-student interactions. This paper advocates for a research agenda exploring AI’s role in shaping achievement emotions and calls for a broader shift in educational research toward leveraging AI for meaningful and transformative learning experiences.